Reliable deception cues training in an interactive video game. (August 2018) - Dunbar, Norah E.; Miller, Claude H.; Lee, Yu-Hao; Jensen, Matthew L.; Anderson, Chris; Adams, Aubrie Serena; Elizondo, Javier; Thompson, William; Massey, Zach; Nicholls, Spencer B.; Ralston, Ryan; Donovan, Jaise; et al.
Abstract: Well-designed video games can teach people to decrease their reliance on heuristics and biases, especially in deception detection, where people might be resistant to training or unaware that training is needed. We created the serious game VERITAS in which users ask questions of pre-recorded actors and attempt to determine the veracity of the answers supplied. The efficacy of the game was tested in two different experiments with college student players. We hypothesized that reducing reactance and enhancing self-affirmation of players would mitigate the resistance to training about bias relevant to a deception detection context. We found that compared to a traditional lecture, VERITAS players were more engaged and motivated by the training and outperformed the traditional lecture in training participants about their knowledge of deception cues, and to identify truthful statements but not deceptive ones. The players of VERITAS also showed improvement from the first to the second scenario in the game. These results reveal that perhaps truth and deception detection are separate skills which require different types of training. Highlights: VERITAS is a game for teaching reliable deception detection skills in two scenarios. Compared to a traditional training, game players found VERITAS more engaging. VERITAS players gained more deception knowledge than in traditional training. VERITAS players improved more in truth detection skills than deception detection. Across game scenarios, players improved approximately 10% in deception assessments.